1999
DOI: 10.1007/bf01365264
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diagnosis of impacted upper canines in panoramic radiographs and computed tomographs

Abstract: Ten orthodontists were asked to diagnose the number of impacted upper canines and the number of resorbed lateral and/or central incisor roots in 30 panoramic radiographs (P1) from 30 patients. In order to objectify these diagnoses, transversal CT images of all 30 patients were examined in addition. Addition of the recordings in the 30 patients revealed that the 10 orthodontists had diagnosed 350 impacted/displaced canines. On comparison of the P1 and CT results, the latter revealed that, in fact, 390 canines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
11
0
7
Order By: Relevance
“…The aforementioned advantages of MSCT technology, namely the accurately-dimensioned representation of anatomical structures free of overlapping images, are accompanied by relatively high levels of radiation exposure for the patient [13,17,18,24]. The effective amount of radiation using the Somatom 64® multi-line CT technique depends on the volume to be scanned (FOV = field of view) and the examination parameters selected [29].…”
Section: Diskussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned advantages of MSCT technology, namely the accurately-dimensioned representation of anatomical structures free of overlapping images, are accompanied by relatively high levels of radiation exposure for the patient [13,17,18,24]. The effective amount of radiation using the Somatom 64® multi-line CT technique depends on the volume to be scanned (FOV = field of view) and the examination parameters selected [29].…”
Section: Diskussionmentioning
confidence: 99%
“…Die oben genannten Vorteile des MSCT, wie die dimensionsgetreue überlagerungsfreie Darstellung anatomischer Strukturen, gehen allerdings mit einer relativ hohen Strahlenbelastung für den Patienten einher [13,17,18,24]. Die effektive Strahlendosis ist beim Mehrzeilen-CT Somatom 64® abhängig vom abzubildenden Volumen ("field of view", FOV) und den gewählten Untersuchungsparametern [29].…”
Section: Conflict Of Interestunclassified
“…However, panoramic radiography has limitations in assessing the labiopalatal position of impacted canines and root resorption of incisors. 8 The relatively high radiation dose and cost have restricted multidetector CT (MDCT) use in the evaluation of tooth impaction. 9 The radiation dose of cone beam CT (CBCT) is significantly lower than MDCT and the typical overlap of dental structures visualized on panoramic radiographs is not observed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that volumetric CT data are suitable for taking linear measurements and determining angles [3,6,10,15,23,25,26,33,35]. Thanks to Titiz et al…”
Section: Discussionmentioning
confidence: 99%
“…Die Eignung von volumetrischen CT-Daten für lineare Messungen oder die Bestimmung von Winkeln wurde bereits in früheren Studien nachgewiesen [3,6,10,15,23,25,26,33,35]. Da die Genauigkeit und Messpunktreproduzierbarkeit in dreidimensionalen CT-Datensätzen bereits von Titiz et al [47] ausführlich untersucht und belegt wurde, konnte hier auf Mehrfachmessungen und somit die Untersuchung des Interund Intrauntersucherfehlers verzichtet werden.…”
Section: Diskussionunclassified